Lipidic cubic phase injector is a viable crystal delivery system for time-resolved serial crystallography - Przemyslaw Nogly (Nature Portfolio, 2016)
Serial femtosecond crystallography using X-ray free-electron lasers has huge potential for time-resolved structural experiments. Here, the authors present a structure of the light-driven proton pump bacteriorhodopsin using these techniques.